Feed additives - James R. Dunham (Kansas Agricultural Experiment Station Research Reports, 1986)
Feed additives are ration ingredients used in relatively small amounts to fortify certain nutrients or to affect a specific physiological function. The decision to include any additive should be based upon the economic response expected. The following guidelines are designed to help identify situations where additives may be considered.; Dairy Day, 1986, Kansas State University, Manhattan, KS, 1986;
Keywords: Kansas Agricultural Experiment Station contribution; no. 87-88-S; Report of progress (Kansas Agricultural Experiment Station); 506; Dairy; Feed additives; Minerals; Trace minerals; Vitamins; Amino acids; Fats; Buffers